Gradient heterogeneous structure for improving high-temperature oxidation resistance of alloy, preparation method of gradient heterogeneous structure and alloy

By forming a gradient isomerial structure on the surface of the alloy, the synergistic effect of the gradient distribution grain size, annealing twin boundaries and precipitation phases, the problem of the oxide film peeling of existing heat-resistant stainless steel at high temperatures is solved, and the high-temperature oxidation resistance and strength performance of the alloy is significantly improved.

CN119571047APending Publication Date: 2025-03-07INST OF HIGH ENERGY PHYSICS CHINESE ACAD OF SCI +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411752969.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The existing heat-resistant austenitic stainless steel is prone to repeated peeling of oxide films in high-temperature oxidation environments, resulting in pipe bursting, and cannot meet the high-temperature oxidation resistance and long-lasting creep performance requirements of 700℃ grade ultra-supercritical power generation technology.

Method used

Gradient isomeric structure is adopted, and the grain size is distributed inward from the alloy surface through surface treatment, and a large number of annealing twin boundaries and precipitation phases are formed through annealing treatment, which synergistically improves the high-temperature oxidation resistance of the alloy.

Benefits of technology

It significantly improves the high-temperature oxidation resistance of the alloy, reduces the rate of oxidation reaction, enhances the anti-peeling ability of the oxide film, and improves the high-temperature strength and creep resistance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571047A_ABST
    Figure CN119571047A_ABST
Patent Text Reader

Abstract

The invention relates to a gradient heterogeneous structure for improving the high-temperature oxidation resistance of an alloy, a preparation method of the gradient heterogeneous structure and the alloy. The gradient heterogeneous structure comprises an alloy structure extending from the surface of the alloy to the interior. In the gradient heterogeneous structure, the grain size is in gradient distribution inwards from the surface of the alloy; in the gradient heterogeneous structure, crystal grains in the same depth range are distributed in multiple sizes, namely, the crystal grains are heterogeneous; annealing twin boundaries exist in the crystal grains; and a precipitated phase exists in the crystal grains or along the crystal boundary. The gradient heterogeneous structures provided by the invention are in gradient distribution in the depth direction macroscopically, grain heterogeneous structures with large grain size difference are locally formed in the same depth range, annealing twin boundaries and precipitated phases are formed in grains, and the high-temperature oxidation resistance of the alloy can be improved while the high-temperature strength of the alloy can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface engineering, and in particular to a gradient isomerization structure for improving high-temperature oxidation resistance of an alloy, a preparation method thereof, and an alloy. Background Art

[0002] With the development of ultra-supercritical power generation technology, reducing coal consumption of thermal power units has become an important direction for the development of power equipment. At present, the ultra-supercritical power stations currently in operation are mainly 600-630℃ grade. Based on performance and cost considerations, core components such as superheaters and heat exchangers still widely use heat-resistant austenitic stainless steels such as Super304H and HR3C. However, during the long-term service of the above-mentioned heat-resistant stainless steel in a high-temperature oxidizing environment, it is easy to produce the problem of repeated peeling of the oxide film, resulting in oxide blocking the pipeline and causing pipe bursting, which brings great difficulties to the maintenance of the unit and poses a threat to safe operation.

[0003] In addition, as ultra-supercritical power generation technology develops towards the 700℃ level, the existing heat-resistant austenitic stainless steel can no longer meet the requirements of high-temperature oxidation resistance and long-lasting creep performance. Although existing studies have shown that new nickel-based or iron-nickel-based high-temperature alloys have broad application prospects in ultra-supercritical units with higher temperature levels, the above-mentioned high-temperature alloys also have abnormal oxidation phenomena during service. The outdiffusion of metal oxygen cations caused by surface oxidation will not only form defects such as holes near the oxide film / matrix interface, but also lead to coarsening of surface grains and the formation of precipitation-free phase areas. These factors will lead to a decrease in the creep strength of the material, accelerate the initiation and propagation of cracks on the surface, and shorten the creep life of the alloy.

[0004] The high-temperature oxidation behavior of alloys is determined by the chemical composition and microstructure of their surface. By regulating the grain size, grain boundary type and precipitation behavior of their surface, it is expected that the high-temperature oxidation resistance will be improved. Therefore, based on the objective demand for improving the high-temperature oxidation resistance of alloys, how to improve the high-temperature oxidation resistance of alloys by regulating the surface microstructure is a technical problem that needs to be solved in this field. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a gradient isomerization structure and a preparation method and alloy for improving the high temperature oxidation resistance of the alloy. Compared with the prior art, the gradient isomerization structure provided by the present invention is macroscopically distributed in a gradient along the depth direction, and locally forms grain isomerization with large grain size differences within the same depth range, and forms annealing twin boundaries and precipitation phases inside the grains, which can improve the high temperature strength of the alloy while improving its high temperature oxidation resistance.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a gradient isomerization structure for improving the high temperature oxidation resistance of an alloy, wherein the gradient isomerization structure comprises an alloy structure extending from the surface of the alloy to the inside;

[0008] In the gradient heterogeneous structure, the grain size is distributed in a gradient from the alloy surface to the inside;

[0009] In the gradient heterogeneous structure, the grains within the same depth range are distributed in multiple sizes, that is, the grains are heterogeneous;

[0010] There are annealing twin boundaries inside the grains;

[0011] There are precipitated phases inside the grains or along the grain boundaries.

[0012] The gradient isomerization structure provided by the present invention mainly regulates the microstructure of the alloy from three aspects: on the one hand, the grain size is distributed in a gradient from the surface of the alloy to the inside, that is, the grains are from small to large from the outside to the inside, and the grain boundary ratio is increased by refining the surface grains, thereby improving the oxidation resistance of the alloy; on the one hand, the diffusion behavior of elements at high temperatures is affected by annealing the twin boundaries, and the twin boundaries can avoid the phenomenon that conventional grain boundaries promote the diffusion of oxygen elements along the grain boundaries and internal oxidation, and the twin boundaries can improve the strength of the alloy and inhibit the occurrence of internal oxidation; on the other hand, the precipitation phase precipitates along the grain boundaries or in the grains, which can inhibit the diffusion of elements along the grain boundaries and the inward growth of the oxide film, thereby reducing the rate of the oxidation reaction. In summary, the gradient isomerization structure provided by the present invention can effectively improve the high-temperature oxidation resistance of the alloy by regulating the microstructure of the alloy surface.

[0013] In the present invention, the “multi-size distribution” refers to that the size of the grains within the same depth range is not a single size, but includes grains of different sizes, that is, the grains are heterogeneous.

[0014] Preferably, the surface thickness of the gradient isomerized tissue is 5-80 μm, for example, it can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm or 80 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the total thickness of the gradient isomerized tissue is 100-1500 μm, for example, it may be 100 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, 1100 μm, 1200 μm, 1300 μm, 1400 μm or 1500 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0016] In the present invention, the total thickness of the gradient heterogeneous structure is affected by the surface treatment process and is selected and set according to the performance requirements of high-temperature oxidation resistance.

[0017] Preferably, the maximum grain size in the surface layer is 2-5 times the minimum grain size, for example, 2 times, 3 times, 4 times or 5 times, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] Preferably, the equivalent diameter of the grains in the surface layer is 0.08-5μm, for example, it can be 0.08μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In the present invention, the size of the crystal grains is affected by the annealing process, and it is preferred to control the equivalent diameter of the crystal grains in the surface layer within a specific range. If the crystal grain size is too large, the grain boundary ratio per unit area is reduced, and it cannot provide sufficient protective oxide film-forming elements as an element diffusion channel to maintain the stability of the oxide film. When the crystal grain size is small, its thermal stability is low, and it is easy to grow due to the diffusion of grain boundary elements during the oxidation process.

[0020] Preferably, the grains of the gradient isomerized structure are nearly equiaxed.

[0021] Preferably, the proportion of annealed twin boundaries in the gradient isomerized structure to total grain boundaries is 40-70%, for example, it can be 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68% or 70%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the size of the precipitated phase in the gradient isomerized structure is 30-500nm, for example, it can be 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm, 480nm or 500nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] Preferably, the precipitated phase includes any one of a Cu-rich precipitated phase, a Sigma phase, a Laves phase or a γ′ phase, or a combination of at least two of them.

[0024] Preferably, the number density of the precipitated phase in the gradient isomerized structure is 3-5 times that of the alloy matrix, for example, 3 times, 4 times or 5 times, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In the present invention, the "alloy matrix" refers to the remaining portion of the alloy excluding the outermost gradient heterogeneous structure.

[0026] Preferably, the alloy includes any one of stainless steel, nickel-based high-temperature alloy, iron-nickel-based high-temperature alloy, titanium alloy or high-entropy alloy.

[0027] Preferably, the elements contained in the alloy include any one or a combination of at least two of C, N, Fe, Cr, Mn, Al, Ni, Nb, Cu, Ti, V, Mo, W, B, Zr, Co or Ce.

[0028] In the present invention, the type of the precipitated phase is affected by the alloy composition. In the present invention, it is preferably applicable to stainless steel, nickel-based high-temperature alloy, iron-nickel-based high-temperature alloy, titanium alloy or high-entropy alloy containing the above elements.

[0029] In a second aspect, the present invention provides a method for preparing a gradient isomerized structure for improving the high temperature oxidation resistance of the alloy as described in the first aspect of the present invention, the preparation method comprising the following steps:

[0030] (1) Surface treatment of the alloy is performed to make the grain size distribute in a gradient from the alloy surface to the inside, thereby obtaining a gradient structure;

[0031] (2) Annealing the gradient structure obtained in step (1) to obtain a gradient heterogeneous structure.

[0032] In the present invention, firstly, surface treatment is performed to make the grain size distribute in a gradient from the alloy surface to the inside, so as to achieve grain refinement and introduce residual stress on the alloy surface, and then annealing treatment is performed to further control the microstructure of the alloy, so as to obtain a large number of twin boundaries and precipitated phases.

[0033] Preferably, the surface treatment method in step (1) includes any one of laser shock peening, shot peening, surface mechanical grinding or surface mechanical rolling, or a combination of at least two of them.

[0034] In the present invention, the laser shock strengthening, shot peening, surface mechanical grinding or surface mechanical rolling methods can all adopt conventional methods for obtaining gradient structures in the art. The parameters of the above methods can be set according to the needs of gradient heterogeneous structures, wherein the conditions of laser shock strengthening can be, for example: a 0.5 mm thick aluminum foil is attached to the surface of the alloy sample as an absorption layer, a 1-2 mm thick water is used as a constraint layer, the laser energy used is 5-8 J, the laser wavelength is 1054-1064 nm, the pulse width is about 10 ns, the spot diameter is 3 mm, and the repetition is 100 ns. The frequency is 1Hz; the operating conditions of the shot peening process can be, for example: using ceramic micro beads with a particle size of 0.5-1mm, an air pressure of 0.4-0.6MPa, a shot peening flow rate of 1.5-1.8kg / min, and a processing time of 3-5 minutes; the conditions for surface mechanical rolling can be, for example: rotating the alloy sample at a speed of 100-400r / min, feeding the rolling head along the axis direction of the sample at a speed of 0.01-0.02mm / r, and performing 1-5 surface treatments on the alloy sample, with a pressure of 0.3-2.0MPa for each pass.

[0035] Preferably, the temperature of the annealing treatment in step (2) is 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] In the present invention, the temperature of the annealing treatment is preferably controlled within a specific range, which is conducive to the formation and controllable preparation of a gradient isomerization structure. If the temperature is too low, recrystallization cannot occur to form a gradient isomerization structure, and if the temperature is too high, the grains will grow and coarsen rapidly. In the present invention, if the ambient temperature of the alloy service is within the range of this annealing temperature, the alloy after surface treatment can be directly placed in the service environment to obtain a gradient isomerization structure.

[0037] Preferably, the annealing time is 5-15 min, for example, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 12 min or 15 min, but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable.

[0038] In a third aspect, the present invention provides an alloy comprising the gradient isomerized structure for improving the high temperature oxidation resistance of the alloy as described in the first aspect of the present invention.

[0039] The alloy provided by the present invention has good high-temperature strength and creep resistance, as well as good high-temperature oxidation resistance by adopting the above-mentioned gradient isomerization structure.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] (1) In the gradient isomerized structure and alloy thereof provided by the present invention, the high temperature strength and creep resistance of the alloy can be effectively improved by forming a large number of precipitation phases and synergistic effects of annealing twin boundaries.

[0042] (2) The gradient heterogeneous structure provided by the present invention can greatly improve the oxidation resistance of the alloy in a high temperature environment (≤1000°C), and the thickness of the oxide film and the oxidation reaction rate are greatly reduced, and the anti-stripping ability of the oxide film is enhanced. Specifically, taking the high-temperature oxidation resistance evaluation experiment of 700°C as an example, the thickness of the oxide film is only 1 / 20 of that of the coarse-grained sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 A gradient heterogeneous tissue morphology diagram provided in Example 1 of the present invention;

[0044] Figure 2 for Figure 1 A partial enlarged view of the middle A;

[0045] Figure 3 A grain boundary distribution diagram of the surface layer of the gradient heterogeneous structure provided in Example 1 of the present invention;

[0046] Figure 4 The precipitation phase distribution diagram of the surface layer of the gradient heterogeneous structure provided in Example 1 of the present invention, wherein Figure 4 (a) is the morphology of the surface precipitation phase; Figure 4 (b) Figure 4 (a) Distribution diagram of Cu element; Figure 4 (c) Figure 4 (a) Distribution diagram of Cr element;

[0047] Figure 5 This is a cross-sectional morphology diagram of the alloy after surface treatment in Example 1 of the present invention;

[0048] Figure 6 The precipitation phase distribution diagram of the surface layer of the coarse-grained sample provided in Comparative Example 1 of the present invention, wherein Figure 6 (a) is the morphology of the surface precipitation phase; Figure 6 (b) Figure 6 (a) Distribution diagram of Cu element; Figure 6 (c) Figure 6 (a) Distribution diagram of Cr element;

[0049] Figure 7 In the figure: (a) is a surface morphology of the oxide film of the coarse-grained sample provided in Comparative Example 1; (b) is a partial enlarged view of (a); (c) is a surface morphology of the oxide film of the alloy sample containing a gradient isomerized structure provided in Example 1; (d) is a partial enlarged view of (c);

[0050] Figure 8 In the figure: (a) is a cross-sectional morphology of the oxide film of the coarse-grained sample provided in Comparative Example 1; (b) is a cross-sectional morphology of the oxide film of the alloy sample containing a gradient isomerization structure provided in Example 1;

[0051] Fig. 9 This is a cross-sectional morphology of the oxide film after annealing of the alloy provided in Comparative Example 3 of the present invention;

[0052] Fig.10 In the figure: (a) is a cross-sectional morphology of the oxide film of the alloy sample in Example 2 of the present invention; (b) is a cross-sectional morphology of the oxide film of the alloy sample in Example 3 of the present invention;

[0053] Fig.11 is a cross-sectional morphology of the oxide film of the alloy sample in Example 5 of the present invention;

[0054] Fig.12 A grain boundary distribution diagram of the surface layer of the gradient heterogeneous structure provided in Example 6 of the present invention;

[0055] Fig.13 In: (a) is a morphology of the precipitation phase of the surface layer of the gradient heterogeneous structure provided in Example 6 of the present invention; (b) is a local enlarged view of B in (a);

[0056] Fig.14 In the figure: (a) is a cross-sectional morphology of the oxide film of an alloy sample containing a gradient isomerized structure provided in Example 6 of the present invention; (b) is a cross-sectional morphology of the oxide film of a coarse-grained sample provided in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0057] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0058] In the following examples and comparative examples, a Verios 5UC high-resolution field emission scanning electron microscope was used to observe the alloy cross-section, gradient heterogeneous structure morphology, oxide film surface morphology and oxide film cross-sectional morphology, and a Talos F200XG2 field emission transmission electron microscope was used to detect the precipitate phase morphology and element distribution.

[0059] Example 1

[0060] This embodiment provides a gradient isomerization structure for improving the high temperature oxidation resistance of an alloy, wherein the gradient isomerization structure includes an alloy structure extending from the alloy surface to the inside, wherein the grain size is gradiently distributed from the alloy surface to the inside, and the grains within the same depth range are distributed in multiple sizes, i.e., the grains are isomerization, and there are annealing twin boundaries inside the grains, and there are precipitated phases inside the grains or along the grain boundaries, and the grains in the gradient isomerization structure are nearly equiaxed;

[0061] In this embodiment, the alloy is Super304H type heat-resistant austenitic stainless steel, and its chemical composition, measured by mass percentage, includes: 18.46% Cr, 9.12% Ni, 0.09% C, 0.12% N, 0.61% Mn, 0.49% Nb, 3.04% Cu, 0.21% Si, 0.015% P, 0.005% S, and the balance is Fe and other inevitable impurities; its microstructure is single austenite;

[0062] In this embodiment, the morphology of the gradient heterogeneous structure is as follows: Figure 1 As shown, from Figure 1 It can be seen that the grains are distributed in a gradient from small to large from the surface to the inside. Figure 1 The enlarged part A in the middle is as follows Figure 2 As shown, from Figure 2 It can be seen that the grains within the same depth range are distributed in multiple sizes, with the largest grain size being 2–5 times the smallest grain size;

[0063] In this embodiment, the total thickness of the gradient isomerization structure is 450 μm, the thickness of the surface layer is 75 μm, the average grain size of the surface layer is 0.8 μm, and the grain boundary distribution diagram of the surface layer is as follows: Figure 3 As shown, Figure 3 The red line indicates the 5-15° grain boundary, the black line indicates the >15° grain boundary, and the yellow line indicates the twin boundary. Figure 3 It can be seen that there are a large number of annealing twin boundaries in the grains, accounting for about 48%;

[0064] In this embodiment, the morphology of the surface precipitated phase is as follows: Figure 4 (a) shows the distribution of Cu and Cr. Figure 4 (b) and Figure 4 As shown in (c), it can be seen that the precipitated phase includes a large amount of Cu-rich precipitated phase and a small amount of Cr-rich Sigma phase. The size of the precipitated phase is 20-80nm, and the number density of the precipitated phase is 5.5×10 13 / m 2 .

[0065] This embodiment also provides a method for preparing the above-mentioned gradient isomerization structure for improving the high temperature oxidation resistance of the alloy, and the preparation method comprises the following steps:

[0066] (1) The alloy is surface treated so that the grain size is distributed in a gradient from the alloy surface to the inside, and a gradient structure is obtained. The cross-sectional morphology of the alloy after surface treatment is as follows: Figure 5 As shown;

[0067] The surface treatment shown adopts the surface mechanical rolling method, specifically: the alloy sample (round bar with a diameter of 6 mm) is clamped on the rotation system of the lathe and rotated at a speed of 300 r / min, and a rolling head (WC / Co alloy) with a diameter of 7 mm is pressed into the surface of the alloy sample. The rolling head feeding system feeds along the sample axis at a speed of V=0.017 mm / r. The alloy sample is subjected to 5 passes of surface treatment, and the pressure of each pass is 0.5 MPa, 0.8 MPa, 1.2 MPa, 1.6 MPa and 2.0 MPa respectively. During the process of surface mechanical rolling, the sample surface is lubricated and cooled by lubricating oil, so that the surface grains from the surface to the depth of 450 μm are refined compared with the initial grains inside.

[0068] (2) The gradient structure obtained in step (1) is annealed in a muffle furnace at 700° C. for 10 min to obtain a gradient isomerized structure. The morphology of the gradient isomerized structure is shown in FIG. Figure 1 shown.

[0069] This embodiment also provides an alloy containing the above-mentioned gradient heterogeneous structure.

[0070] Comparative Example 1

[0071] This comparative example provides an alloy, which is the Super304H heat-resistant austenitic stainless steel in Example 1, but is not subjected to surface treatment and annealing treatment, and is recorded as a coarse-grained sample.

[0072] The alloy sample containing the gradient isomerization structure in Example 1 and the coarse-grained sample in Comparative Example 1 were oxidized in an air environment at 700°C for 100 hours to perform a high-temperature oxidation resistance evaluation experiment. After the high-temperature oxidation resistance evaluation experiment, the morphology of the surface precipitation phase of the coarse-grained sample provided in Comparative Example 1 is as follows: Figure 6 (a) shows the distribution of Cu and Cr. Figure 6 (b) and Figure 6 (c) Figure 6 The area corresponding to the Cr element in (c) is the Cr2O3 oxide film, and the area below is the alloy matrix. It can be seen that the number density of the precipitated phase in the alloy matrix in Comparative Example 1 is 1.2×10 13 / m 2 , while the number density of the surface precipitated phase in Example 1 is 5.5×10 13 / m 2 , which is about 4.6 times that of Comparative Example 1.

[0073] Comparative Example 1 Compared with Example 1, the surface of the oxide film of the coarse-grained sample in Comparative Example 1 is as follows Figure 7 (a) and Figure 7 As shown in (b), it can be seen that a large number of nodular iron-rich oxides are formed on the surface. The surface of the oxide film of the alloy sample containing the gradient isomerization structure in Example 1 is as follows: Figure 7 (c) and Figure 7 As shown in (d), it can be seen that the oxide on its surface is a uniform spinel oxide; the cross-section of the oxide film of the coarse-grained sample and the alloy sample containing gradient isomerization structure is analyzed, as shown in Figure 8 (a) and Figure 8 As shown in (b), the results show that the coarse-grained sample in Comparative Example 1 undergoes internal oxidation and contains an inner oxide layer and an outer oxide layer, and the thickness of the oxide film is about 20 times that of the alloy sample containing a gradient isomerized structure in Example 1.

[0074] Comparative Example 2

[0075] This comparative example provides an alloy, which is the Super304H heat-resistant austenitic stainless steel in Example 1, and is only surface treated in the same manner as in Example 1, without annealing.

[0076] Compared with Example 1, although the alloy provided in Comparative Example 2 can obtain a surface structure composed of gradient nanograins (i.e., gradient structure) through surface treatment, it is not stable at high temperatures and will rapidly grow grains. During long-term service in a high-temperature oxidizing environment, the changes in grain size, precipitated phases, and grain boundaries are difficult to control, and its antioxidant performance is difficult to guarantee.

[0077] Comparative Example 3

[0078] This comparative example provides an alloy, which is the Super304H heat-resistant austenitic stainless steel in Example 1, and is only annealed in the same manner as in Example 1, without surface treatment.

[0079] Comparative Example 3 Compared with Example 1, the alloy sample containing gradient isomerization structure provided in Example 1 has excellent high temperature oxidation resistance, while the alloy in Comparative Example 3 undergoes abnormal oxidation after annealing, and the cross section of the oxide film is as follows: Fig. 9 As shown, from Fig. 9 It can be seen that the alloy in Comparative Example 3 underwent severe internal oxidation after annealing.

[0080] Example 2

[0081] This embodiment provides a method for preparing a gradient isomerized structure for improving the high-temperature oxidation resistance of an alloy. The only difference compared with Embodiment 1 is that the annealing temperature is 550°C.

[0082] Example 3

[0083] This embodiment provides a method for preparing a gradient isomerized structure for improving the high-temperature oxidation resistance of an alloy. The only difference compared with Embodiment 1 is that the annealing temperature is 800°C.

[0084] Example 2-3 can also obtain a gradient isomerization structure. The alloy samples containing the gradient isomerization structure provided by Example 2-3 were oxidized in an air environment at 700°C for 100h to conduct a high temperature oxidation resistance evaluation experiment. The results are as follows: Fig.10 (a) and Fig.10 As shown in (b), the results show that the alloy samples of Examples 2-3 did not undergo abnormal oxidation, and the thickness of the oxide film was 0.8-1.8 μm, indicating that both groups of samples have excellent high-temperature oxidation resistance.

[0085] Example 4

[0086] This embodiment provides a method for preparing a gradient isomerized structure for improving the high-temperature oxidation resistance of an alloy. The only difference compared with Embodiment 1 is that the annealing temperature is 450°C.

[0087] Example 5

[0088] This embodiment provides a method for preparing a gradient isomerized structure for improving the high-temperature oxidation resistance of an alloy. The only difference compared with Embodiment 1 is that the annealing temperature is 900°C.

[0089] Compared with Example 4-5, the annealing temperature in Example 4-5 is not within the preferred range of the present invention. The alloy samples in Example 4-5 were oxidized in an air environment at 700°C for 100h to conduct a high-temperature antioxidant performance evaluation experiment, and their antioxidant effect is not as good as that of Example 1. Because when annealed at 450°C, due to the annealing temperature being too low, its surface layer is still gradient nanocrystalline, and the gradient heterogeneous structure in the present invention cannot be obtained. The surface nanocrystalline grains will accelerate the oxidation reaction rate in the early stage of the oxidation reaction. When the temperature is 900°C, the surface grains recrystallize and grow rapidly, resulting in a decrease in the grain boundary ratio, and it is impossible to provide sufficient protective oxide film-forming elements through grain boundary diffusion. In addition, the second phase cannot be precipitated in large quantities at the grain boundaries at high temperatures. The cross-sectional morphology of the oxide film of the alloy sample in Example 5 is as shown in FIG. Fig.11 As shown, the thickness of the oxide film in Example 5 is about 10 μm and contains many microcracks, so its high temperature oxidation resistance is not as good as that of Example 1. It can be seen that the present invention can further obtain a gradient heterogeneous structure and improve the high temperature oxidation resistance by preferably controlling the temperature of the annealing treatment.

[0090] Example 6

[0091] The present embodiment provides a gradient isomerization structure for improving the high temperature oxidation resistance of an alloy, wherein the gradient isomerization structure includes an alloy structure extending from the surface of the alloy to the inside, wherein the grain size is distributed in a gradient from small to large from the surface of the alloy to the inside, and the grains within the same depth range are distributed in multiple sizes, and the maximum grain size is 2-5 times the minimum grain size, i.e., the grains are heterogeneous, and there are annealing twin boundaries inside the grains, and there are precipitated phases inside the grains or along the grain boundaries, and the grains in the gradient isomerization structure are nearly equiaxed;

[0092] In this embodiment, the alloy is 304H type heat-resistant austenitic stainless steel, and its chemical composition, measured by mass percentage, includes: 17.83% Cr, 8.21% Ni, 0.06% C, 0.52% Mn, 0.42% Cu, 0.31% Si, 0.012% P, 0.007% S, and the balance is Fe and other inevitable impurities; its microstructure is single austenite;

[0093] In this embodiment, the total thickness of the gradient isomerization structure is 200 μm, the thickness of the surface layer is 45 μm, the average grain size of the surface layer is 1.6 μm, and the grain boundary distribution diagram of the surface layer is as follows: Fig.12 As shown, Fig.12 The black line in the middle indicates the >15° grain boundary, and the yellow line indicates the twin boundary. Fig.12 It can be seen that there are a large number of annealing twin boundaries in the grains, accounting for about 42%;

[0094] In this embodiment, the morphology of the surface precipitated phase is as follows: Fig.13 As shown in (a), Fig.13 The local enlarged image of point B in (a) is shown in Fig.13 As shown in (b), it can be seen that the gradient isomerized structure provided in this embodiment contains a large amount of Sigma precipitation phase, and the number density is much higher than that in the internal alloy matrix.

[0095] This embodiment also provides a method for preparing the above-mentioned gradient isomerization structure for improving the high temperature oxidation resistance of the alloy, and the preparation method comprises the following steps:

[0096] (1) Surface treatment of the alloy is performed to make the grain size distribute in a gradient from the alloy surface to the inside, thereby obtaining a gradient structure;

[0097] The surface treatment shown adopts the surface mechanical rolling method, specifically: the alloy sample (round bar with a diameter of 6 mm) is clamped on the rotation system of the lathe and rotated at a speed of 300 r / min, and a rolling head with a diameter of 7 mm (WC / Co alloy) is pressed into the surface of the alloy sample. The rolling head feeding system feeds along the sample axis direction at a speed of V=0.017 mm / r, and the alloy sample is subjected to 5 passes of surface treatment, and the pressure of each pass is 0.3 MPa, 0.5 MPa, 0.8 MPa, 1.1 MPa and 1.3 MPa, respectively. During the process of surface mechanical rolling, the sample surface is lubricated and cooled by lubricating oil, so that the surface grains from the surface to a thickness of 200 μm are refined compared with the internal initial grains;

[0098] (2) The gradient structure obtained in step (1) is annealed in a muffle furnace at 650° C. for 10 min to obtain a gradient heterogeneous structure.

[0099] This embodiment also provides an alloy containing the above-mentioned gradient heterogeneous structure.

[0100] Comparative Example 4

[0101] This comparative example provides an alloy, which is the 304H type heat-resistant austenitic stainless steel in Example 6, without surface treatment and annealing treatment, and is recorded as a coarse-grained sample.

[0102] Comparative Example 4 Compared with Example 6, the alloy sample containing the gradient isomerization structure in Example 6 and the coarse-grained sample in Comparative Example 4 were oxidized in air at 650°C for 100h to carry out a high-temperature oxidation resistance evaluation experiment. The results are as follows: Fig.14 (a) and Fig.14 As shown in (b), it can be seen that the oxide film thickness in Example 6 is extremely thin, while the oxide film thickness in Comparative Example 4 exceeds 35 μm and many microcracks appear in the oxide film. It can be seen that the high-temperature oxidation resistance of Example 6 is significantly better than that of Comparative Example 4.

[0103] In summary, the gradient isomerization structure provided by the present invention is macroscopically distributed in a gradient along the depth direction, and locally forms grain isomerization with large grain size differences within the same depth range, and forms annealing twin boundaries and precipitation phases inside the grains, which can improve the high-temperature strength of the alloy while improving its high-temperature oxidation resistance.

[0104] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A gradient isomerization structure for improving the high temperature oxidation resistance of an alloy, characterized in that: The gradient heterogeneous structure includes an alloy structure extending from the alloy surface to the inside; In the gradient heterogeneous structure, the grain size is distributed in a gradient from the alloy surface to the inside; In the gradient heterogeneous structure, the grains within the same depth range are distributed in multiple sizes, that is, the grains are heterogeneous; There are annealing twin boundaries inside the grains; There are precipitated phases inside the grains or along the grain boundaries.

2. The gradient heterogeneous tissue according to claim 1, characterized in that: The surface thickness of the gradient isomerized tissue is 5-80 μm; Preferably, the total thickness of the gradient isomerized tissue is 100-1500 μm; Preferably, the maximum grain size in the surface layer is 2-5 times the minimum grain size.

3. The gradient heterogeneous tissue according to claim 2, characterized in that: The equivalent diameter of the grains in the surface layer is 0.08-5 μm.

4. The gradient heterogeneous tissue according to any one of claims 1 to 3, characterized in that: The grains of the gradient isomerized structure are nearly equiaxed.

5. The gradient heterogeneous tissue according to any one of claims 1 to 4, characterized in that: The proportion of annealing twin boundaries in the gradient heterogeneous structure to total grain boundaries is 40-70%.

6. The gradient heterogeneous tissue according to any one of claims 1 to 5, characterized in that: The size of the precipitated phase in the gradient isomerization structure is 30-500 nm; Preferably, the precipitated phase includes any one or a combination of at least two of a Cu-rich precipitated phase, a Sigma phase, a Laves phase or a γ′ phase; Preferably, the number density of the precipitated phase in the gradient isomerized structure is 3-5 times that in the alloy matrix.

7. The gradient heterogeneous tissue according to any one of claims 1 to 6, characterized in that: The alloy includes any one of stainless steel, nickel-based high-temperature alloy, iron-nickel-based high-temperature alloy, titanium alloy or high-entropy alloy; Preferably, the elements contained in the alloy include any one or a combination of at least two of C, N, Fe, Cr, Mn, Al, Ni, Nb, Cu, Ti, V, Mo, W, B, Zr, Co or Ce.

8. A method for preparing a gradient isomerization structure for improving the high temperature oxidation resistance of an alloy as claimed in any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Surface treatment of the alloy is performed to make the grain size distribute in a gradient from the alloy surface to the inside, thereby obtaining a gradient structure; (2) Annealing the gradient structure obtained in step (1) to obtain a gradient heterogeneous structure.

9. The preparation method according to claim 8, characterized in that: The surface treatment method in step (1) includes any one of laser shock peening, shot peening, surface mechanical grinding or surface mechanical rolling, or a combination of at least two thereof; Preferably, the temperature of the annealing treatment in step (2) is 550-800°C; Preferably, the annealing treatment time is 5-15 minutes.

10. An alloy, characterized in that: The alloy contains a gradient isomerized structure for improving the high temperature oxidation resistance of the alloy as described in any one of claims 1 to 7.

Citation Information

Cited By

  • Device and method for preparing gradient heterogeneous structure nickel-based alloy

    CN120421331A